Research on Reflective High-Speed Multi-Point Confocal Microscopy System - Huiqin Hu; Ning He; Kuangwei Du; Yukun Zhu; Dakai Zhou; Yuan Mi; Yunbo Chen; Junteng Ma; Youhua Chen; Cuifang Kuang (Photonics)
Reflective confocal imaging systems often face challenges in achieving high resolution, imaging speed, and uniformity, particularly for reflective sample imaging. This study introduces a reflective multi-point confocal imaging system designed to improve imaging speed, expand the field of view, and optimize performance for reflective sample imaging using incoherent, telecentric light-emitting diode (LED) illumination. By integrating uniform illumination with microlens arrays and optimizing instantaneous structured illumination microscopy optical components, the system achieves a resolution of 1116 lp/mm (20×, 0.42), 100 fps imaging, and a 500 µm × 500 µm field of view while improving contrast. A comparative analysis of laser- and LED-based scanning demonstrates that incoherent illumination provides superior uniformity and reduces intensity variance in reflective imaging. Validation through photon-reassignment experiments, resolution target imaging, and 100 nm metal particle visualization confirmed the system’s enhanced resolution. Furthermore, ex vivo corneal imaging revealed cellular-level details, suggesting its potential for noncontact corneal diagnostics.